Contract and Commitment: Employment Relations in the New Economy - Russell, Bob (Relations industrielles / Industrial Relations, 2000)
The article reviews the book, "Contract and Commitment: Employment Relations in the New Economy," edited by Anil Verma and Richard P. Chaykowski.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Corporations; Labor Unions; Labor relations; Reorganization; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z